Polymorphism of insulin like growth factor binding protein 3 (IGFBP3) partial gene in mithun - PANIGRAHI, MANJIT; KUMAR, SUBODH; DEB, S M; MITRA, ABHIJIT; CHOWDHARY, HITU; SHARMA, ARJAVA (The Indian Journal of Animal Sciences, 2012)
A fragment of 652 bp corresponding to exon–2–3 of IGFBP3 gene was amplified in 90 mithun (Bos frontalis). The PCR- RFLP analysis showed the absence of polymorphism in this fragment with respect to HinfI restriction enzyme and showed only 2 restriction sites, which produced 3 fragments of 314, 206 and 132 bp (AA genotype). Six single nucleotide differences viz. T34C, C164G, T175C, A354G, T599C and G614A existed in mithun sequences when compared to cattle. The neocleotide and amino acid sequence homology between them was 98.2 and 100% respectively. Mithun had minimum deviation from cattle with respect to nucleotide as well as amino acid sequences. The sequence of the amplicon, which was the first report on mithun IGFBP3, was submitted to GenBank (Accession number EF686017).